2018
DOI: 10.1111/inr.12465
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric pain management: knowledge, attitudes, barriers and facilitators among nurses – integrative review

Abstract: Nursing and health policy should mandate the prioritization of paediatric pain management and the clinical roles and responsibilities of the interdisciplinary team members. Undergraduate, postgraduate and in-service education for nurses and other health professionals should also address paediatric pain management. In-service education on paediatric pain management should be compulsory for all health professionals caring for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 35 publications
3
55
0
14
Order By: Relevance
“…Despite the overall good knowledge score in the current study, the majority of the nurses demonstrated poor knowledge with regard to pain assessment and the use of analgesics in pain management among children. is finding largely agrees with the study by Alotaibi et al [2] in Australia which revealed that nurses recorded poor knowledge in the areas of basic pain assessment and management principles. Also, the study by Anim-Boamah [16] in the southern part of Ghana revealed that nurses demonstrated limited knowledge about pain assessment scales and pharmacological strategies for managing invasive procedural pain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the overall good knowledge score in the current study, the majority of the nurses demonstrated poor knowledge with regard to pain assessment and the use of analgesics in pain management among children. is finding largely agrees with the study by Alotaibi et al [2] in Australia which revealed that nurses recorded poor knowledge in the areas of basic pain assessment and management principles. Also, the study by Anim-Boamah [16] in the southern part of Ghana revealed that nurses demonstrated limited knowledge about pain assessment scales and pharmacological strategies for managing invasive procedural pain.…”
Section: Discussionsupporting
confidence: 91%
“…Pain is a major source of distress for children on admission, parents, and clinicians [1]. Hospitalized children continuously experience unrelieved pain; hence, the provision of effective pain management is an integral and important part of the nurse's role [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, studies have found that many pediatric clinicians focus on the source rather than the symptom (Gaglani, & Gross, 2018; Subhashini, Vatsa, & Lodha, 2009; Twycross, & Dowden, 2009), feeling that in the urgency of saving a life, there is no time to provide effective pain management (Mathews, 2011; Nimbalkar et al, 2014). Many studies have documented that knowledge deficits and negative attitudes of healthcare providers regarding pain management are the most important factors impacting pediatric pain relief care (Mathew et al, 2011; Nimbalkar et al, 2014; Stanley & Pollard, 2013), and that pediatric clinicians' knowledge and attitudes regarding pediatric pain management can affect their willingness to provide such care (Abdulaziz, 2017; Alotabi, Higgins, & Chan, 2019; Alotaibi, Higgins, Day, & Chan, 2018; Bawa, Mahajan, Aggerwal, Sundaram, & Rao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A despeito das evidências científicas supracitadas sobre a reconhecida eficácia de intervenções para dor aguda procedural, buscou-se na literatura as prováveis barreiras que podem explicar o baixo uso dessas intervenções. As dificuldades descritas em pesquisas no âmbito internacional e nacional referem-se a: pouco conhecimento pelos profissionais de saúde dos princípios e atitudes básicas sobre avaliação e manejo da dor (Alotaibi, Higgins, Day, & Chan, 2018), falta de educação continuada no tema (Linhares, Oliveira, Doca, Martinez, Carlotti, & Finley, 2014), tempo insuficiente para preparo dos procedimentos (Czarnecki et al, 2011) e número de profissionais reduzido e carga de trabalho pesada (Twicross, 2013).…”
Section: Associações Entre Indicadores De Dor E Estresse Comportamentunclassified